One-step synthesis of nitrogen-doped graphene supported PdSn bimetallic catalysts for ethanol oxidation in alkaline media. Issue 23 (17th February 2016) - Feng, Yue; Bin, Duan; Zhang, Ke; Ren, Fangfang; Wang, Jin; Du, Yukou
Abstract : In this paper, a facile chemical reduction method was employed to synthesize bimetallic PdSn nanocatalysts, and the nitrogen-doped graphene (N-G) has been used as a conductive support material for PdSn catalysts. Abstract : In this paper, a facile chemical reduction method was employed to synthesize bimetallic PdSn nanocatalysts, and the nitrogen-doped graphene (N-G) has been used as a conductive support material for PdSn catalysts. The structures, morphologies and composition of the catalysts were characterized by transmission electron microscopy (TEM), energy dispersive X-ray spectroscopy (EDX), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS), respectively. Electrochemical measurements such as cyclic voltammetry (CV), chronoamperometry (CA), electrochemical impedance spectrometry (EIS) were carried out to detect the electrochemical activity of the as-prepared catalysts toward ethanol electrooxidation in an alkaline medium. Among the PdSn/N-G catalysts with different molar ratios between Pd and Sn, the free-standing PdSn catalyst and commercial Pd/C catalyst, Pd3 Sn1 /N-G exhibited excellent catalytic activity and stability, indicating that nitrogen-doped graphene as a conductive support material and the moderate addition of Sn can enhance the electrochemical performance of Pd catalysts.